The effects of shocks to interest rate expectations in the euro area: Estimates at the country level - Martin Mandler; Michael Scharnagl (Journal of Forecasting, 2023)
We estimate the effects of shocks to interest rate expectations on the four largest euro area economies. We identify these shocks in a Bayesian vector autoregressive (BVAR) model augmented by survey expectations. We separate the expectations shocks from standard monetary policy shocks by assuming that they do not affect the current policy rate. Our sign restrictions also ensure that these shocks do not contain central bank information shocks. We find that an expected decline in the future short-term rate leads to an increase in output and prices. The increases do not become larger for changes to interest rate expectations further in the future, that is, we do not find evidence of a forward guidance puzzle. Using the multicountry structure of our model, we test for cross-country differences in the shocks' effects and find output and price effects to be greatest in Germany. We also compare the effects of shocks to interest rate expectations to those of standard monetary policy shocks and show the first type to affect output and prices more strongly in Germany and France.
Keywords: 519; Bayesian vector autoregression; euro area; expectations; forward guidance; regional effects of monetary policy; unconventional monetary policy